2018
DOI: 10.2217/fon-2018-0210
|View full text |Cite
|
Sign up to set email alerts
|

Risk–Benefit of Dexrazoxane for Preventing Anthracycline-Related Cardiotoxicity: Re-Evaluating the European Labeling

Abstract: Dexrazoxane can prevent anthracycline-associated cardiotoxicity. However, in 2011, its use in children was contraindicated by the EMA over concerns of increased risk of infection, myelosuppression and second primary malignancies, and because its efficacy in children had not then been established. We review here the evidence published since 2011, which confirms that dexrazoxane is an effective cardioprotectant in children and adolescents, is not associated with an increased risk of second primary malignancies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 47 publications
1
94
0
3
Order By: Relevance
“…In 2017, after reassessment of the data, the contraindication for children and adolescents at risk of cardiotoxicity was removed . The field of oncology has accepted the potential benefits of DRZ . Recently, Liesse et al generated predictions for treatment protocols with and without affiliated DRZ therapy.…”
Section: Strategies For Preventionmentioning
confidence: 99%
“…In 2017, after reassessment of the data, the contraindication for children and adolescents at risk of cardiotoxicity was removed . The field of oncology has accepted the potential benefits of DRZ . Recently, Liesse et al generated predictions for treatment protocols with and without affiliated DRZ therapy.…”
Section: Strategies For Preventionmentioning
confidence: 99%
“…However, despite various therapeutic interventions, the deterioration of the cardiac functions is often accompanied by high mortality rates (8). Dexrazoxane is the only U.S. Food and Drug Administration-approved cardioprotective agent for anthracycline-induced cardiotoxicity (10,11). However, only 26% of patients treated with dexrazoxane tolerate higher cumulative doses of Doxo (12).…”
mentioning
confidence: 99%
“…Patients who receive high doses of anthracyclines are at risk for cardiotoxicity, dexrazoxane is often used as a cardioprotectant when prior doxorubicin reached a cumulative dose of 300 mg/m 2 [32]. But controversy exists if dexrazoxane reduces the antitumor effect of doxorubicin and increases the risk of second primary malignancies [33]. In the present study, we found that there were no differences of EFS and OS in patients with or without administration of dexrazoxane (log-rank test, P > 0.05), and there was no second primary malignancy occurred during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%